2014
DOI: 10.1002/anie.201402789
|View full text |Cite
|
Sign up to set email alerts
|

A Tandem In Situ Peptide Cyclization through Trifluoroacetic Acid Cleavage

Abstract: We present a new approach for peptide cyclization during solid phase synthesis under highly acidic conditions. Our approach involves simultaneous in situ deprotection, cyclization and trifluoroacetic acid (TFA) cleavage of the peptide, which is achieved by forming an amide bond between a lysine side chain and a succinic acid linker at the peptide N-terminus. The reaction proceeds via a highly active succinimide intermediate, which was isolated and characterized. The structure of a model cyclic peptide was solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…This method allows obtaining the macrocyclic product 81 by the formation of an amide bond between a lysine side chain and a succinic acid linker at the peptide N-terminus in 65% yield. 153 On the other hand, different examples for the syntheses of cyclic peptides where the open-chain precursor is previously released from the resin to perform the macrocyclization in solution can also be found in the literature. 154 In nature, the biosynthetic macrocyclization reaction for the formation of macrocyclic peptides is catalyzed by a thioesterase domain at the C-terminal end of the assembly line.…”
Section: Experimental Aspects In the Synthesis Ofmentioning
confidence: 99%
“…This method allows obtaining the macrocyclic product 81 by the formation of an amide bond between a lysine side chain and a succinic acid linker at the peptide N-terminus in 65% yield. 153 On the other hand, different examples for the syntheses of cyclic peptides where the open-chain precursor is previously released from the resin to perform the macrocyclization in solution can also be found in the literature. 154 In nature, the biosynthetic macrocyclization reaction for the formation of macrocyclic peptides is catalyzed by a thioesterase domain at the C-terminal end of the assembly line.…”
Section: Experimental Aspects In the Synthesis Ofmentioning
confidence: 99%
“…Ring opening by piperidine gives a mixture of d / l ‐ α ‐piperidides and d / l ‐ β ‐piperidides. Ring opening by amino groups leads to the formation of dipeptides or cyclic peptides . In most cases, α ‐piperidides and β ‐piperidides are easily separated from the target peptide by RP‐HPLC; however, resolution of the epimerised α ‐aspartyl peptide is very difficult or impossible .…”
Section: Introductionmentioning
confidence: 99%
“…The most potent inhibitors were the LEDGF 361–370 peptide and its cyclic derivatives . Recently we have developed a new peptide cyclization method, in which cyclization between a lysine residue and an N‐terminal succinimide moiety occurs in situ during the TFA‐mediated peptide deprotection/cleavage step . This indicated that the succinimide moiety is susceptible to nucleophilic attack by amine and might be used for covalent inhibition as a precursor for nucleophilic ring opening by nucleophilic amines of the target protein.…”
Section: Introductionmentioning
confidence: 99%